(untitled) (Journal Of Educational and Psychological Researches, 2015)
From the above can be placed in a summary of the Iraqi personal to the subject in the context of urban family Integration: As personal so hard and durable organization to some extent on the nature of the individual temperament, his mind and his body structure Vhoalve determines the unique environment compatibility. Valchksah not inherited However, the inherited components, building of the body of the individual and the way they complement each other and members of Trivhalta functions performed by temperament and preparations all in compliance with Vchksath become a product of the interaction between the possibility of nature and the environment. From here we can say that the family a big role in the personal configuration, the family is the first school of the child as learning through culture and social civilization increase to teach religion and language ... etc., but can not the community alone that complements the personality of the child if it did not pass the first stages of upbringing in the embrace of family and identifies the key character in the future, he said (Freud): the first five years of a child’s life are the foundation on which the human personality and affect it in the future and this means the incubation stage for the family and its importance. It is important when studying personal knowledge of things that pertain to the family in which the individual grew up and which reflects the culture of the community in which the family grew fact play a key and important role in shaping the character and prepare to be a human being socially. It can be seen the effect of changes in the personal and family because of the urbanization process that emerged in the community clearly after the scientific and technological development, which the owner of almost all societies and to varying degrees. Fady to change the family form, construction and functions in and around the extended family to the nuclear family, and family relationships of the dictatorship relations authoritarian absolute Father to the democratic relations and the participation of the mother and the children in the decision-making within the family, and in turn led to a personal style has changed dramatically. As evidence of the researcher through the study that this modest extended family problems were not less than the nuclear family was not the best in the upbringing of the child. Arab and Iraqi ones nuclear family is an unbroken once and for all (family mother), but still the roots of contact existed until now because of its adherence to core values